PELAKSANAAN PERKAWINAN SEDARAH PEMISANAN DITINJAU DARI UNDANG-UNDANG NO. 16 TAHUN 2019 TENTANG PERKAWINAN DAN HUKUM ADAT BALI (Studi Kasus Di Desa Adat Kerobokan, Kecamatan Sawan, Kabupaten Buleleng) - Komang Ary Putra Dharmawan; Ketut Sudiatmaka; Ni Ketut Sari Adnyani (Universitas Pendidikan Ganesha, 2023)
This study aims to (1) To find out and analyze regarding the mechanism and process of implementing inbreeding marriage in Kerobokan Traditional Village, Sawan District, Buleleng Regency (2) To find out and analyze related to community responses and the consequences caused by Kerobokan Traditional Village, District Sawan, Buleleng Regency (3) To assess and analyze the Kerobokan Traditional Village, Sawan District, Buleleng Regency in responding to inbreeding marriages that have not been regulated in awig-awig. The type of research used in this research is empirical legal research. The research location was carried out in the Kerobokan Traditional Village, Sawan District, Buleleng Regency. Data collection techniques using document study techniques, observation and interviews. Qualitative data processing and analysis techniques. The results of the study showed that (1) Some communities in the Kerobokan Traditional Village still carry out inbreeding marriages. (2) Legal Consequences of Inbreed Marriage According to the law in Kerobokan Village. Couples who have been married and have bound themselves will receive consequences between the two parties (husband and wife) which will then give rise to rights and obligations in accordance with applicable law. (3) Efforts for the village community to carry out incest marriages / nganten pemisanan are planned regarding these efforts by socializing the prohibition of marriages and the impacts caused by carrying out incest marriages / nganten pemisanan. In this plan, kelian adat is not alone in preventing this, will be assisted also Seka Truna Truni (STT) and Doctors.